Teaching English to Beginners - Dyas Ayu Anindya (Magister Scientiae, 2010)
English as a foreign language/international language should be introduced and taught to children from early age. Here the writer is limiting only to the children whose age ranges from 6 to 12 years old, those who are sitting in primary school. Young learners at their tender age have the flexibility in their physical as well as their mental domain to feel and make sense of a language. These children enjoy fun activities that will fit to their unique playing world. In their learning activities, listening and speaking will take most of their hours, without neglecting other language skills, i.e. reading and writing. The materials of the lessons will vary depending on their language competence. In teaching young learners a teacher should take into account: teaching materials, class activities, speed, teaching aids, etc. In short, teaching English to young learners need a thorough preparation and planning.